A review on looking at prescription quality in Ayurveda and principles of ethical Ayurvedic prescription (World Journal of Current Medical and Pharmaceutical Research, 2022)
Medical prescriptions have few common generic features, usally containing the basic details of the patient and prescriber identification followed by the medications including its dose, intake schedules and total duration of drug consumption . The importance of prescription quality among every system of medicine an attempt was made to design a prescription quality index for ayurveda. Prescription quality index for ayurveda was found useful in between the ideal and generated prescriptions. Ayurvedic practice of medicine is largely criticized for not utilizing its own concepts of disease, diagnosis and management imposing the modern concepts of pathogenesis and treatments upon their own treatment principles. There is a poor quality of ayurvedic prescriptions is an undercurrent observations and brought into notice frequently. The pilot test was also able to reveal many underlying limitations in contemporary ayurvedic prescription writing. Great caution is warrented while prescribing medicines in children, elders and pregnant ladies and it has been suggested to prescribe disease- specific drugs in limited number of combinations in proper doses with proper adjuvants.